Identification of endophytic actinobacteria from Jerusalem artichoke and examination of inulinase gene and enzyme properties - Wannasutta, Rungnapha; Boonlue, Sophon; Jogloy, Sanun; Mongkolthanaruk, Wiyada (Agriculture and Natural Resources, 2019)
Endophytic actinobacteria isolated from Helianthus tuberosus L. (Jerusalem artichoke) demonstrate great potency in the production of biological function and compounds, including exo-inulinase activity. Exo-inulinase is of interest to the beverage industry, as this enzyme hydrolyzes inulin stored within the Jerusalem artichoke tuber into fructose syrup in a single step. This study aimed to identify and investigate the exo-inulinase-producing endophytic actinobacteria from four varieties of Jerusalem artichoke (HEL65, JA89, CNS2867 and JA102×JA89) in root, leaf and stem samples. In total, 78 isolates of endophytic actinobacteria were classified into 24 different groups based on morphology and then identified based on the 16S rRNA gene into 5 genera: Streptomyces (64.1%), Nocardia (28.2%), Actinosynnema (3.9%), Kribbella (2.6%) and Kineococcus (1.3%). The results of inulinase screening using polymerase chain reaction with degenerated primers showed the specific band at 400 bp of Streptomyces gancidicus EAH-R3 which conserved the protein of the exo-inulinase gene and had inulinase activity of 125 U/mL. This inulinase was confirmed to be an exo-inulinase by checking the end product of inulin hydrolysis using thin layer chromatography. The crude enzyme of S. gancidicus EAH-R3 had an optimum temperature and pH of 60οC and 6.0, respectively. Moreover, the crude inulinase was thermostable at 80οC for 2 hr with a relative activity of 94%. S. gancidicus EAH-R3, a new isolate of endophytic actinobacteria isolated from the plant with high inulin content, is a candidate for fructose production using inulin hydrolysis.